ANALISIS KETERPADUAN PEMBELAJARAN DALAM PEMBUATAN MODUL AJAR IPAS KELAS V SEKOLAH DASAR - Alfiyah Maulani; Anggit Merliana (LPPM Universitas Cipta Mandiri, 2024)
The independent curriculum is an alternative curriculum used post-endemic in the face of learning setbacks which provides freedom with the term